FORECASTING MATERIAL INVENTORY OF PT INALUM (PERSERO) CARBON DEPARTMENT USING SINGLE EXPONENTIAL SMOOTHING METHOD WEB-BASED - Aldi Kesuma; Zulham Sitorus; Wirda Fitriani (Sean Institute, 2022)
An error occurred in recording material inventory, resulting in disruption of the aluminum production process at PT Inalum (Persero). In addition, orders that are not on time can also cause losses to PT Inalum (Persero), because the accumulation of too much material inventory will require a lot of working capital, this allows capital investment for other activities to be hampered, while the limited material inventory allows PT. Inalum (Persero) cannot meet the needs of its customers. The purpose of this study is to determine the amount of material inventory that must be provided by the Carbon Department of PT Inalum (Persero) in the next period. The method used in this study is Single Exponential Smoothing (SES) with the calculation of the error size, namely Mean Absolute Deviation (MAD), Mean Square Error (MSE), and Mean Absolute Perentage Error (MAPE. The results of this study indicate that the calculation of each material uses alpha 0.1 because the lowest percentage of MAPE values is at alpha 0.1 Material Petroleum Coke Low Sulfur has a MAPE percentage of 21.08%, Petroleum Coke High Sulfur has a MAPE percentage of 21.37%, and Diesel has a MAPE percentage namely 17.44%. s Department of Carbon (Persero) using the Single Exponential Smoothing method, it is known that the results of these calculations are the same